(untitled) (Research, Society and Development, 2022)
Temporomandibular Disorders (TMD) are a set of clinical conditions characterized by various signs and symptoms of pain and dysfunction, which directly affect the temporomandibular joint. Depending on the intensity and duration, it is essential that a therapeutic plan is carried out for the cure and/or control of the dysfunction. Therefore, the ideal treatment can only be defined by the Dental Surgeon. In addition to conventional pain management methods, acupuncture is a method of alternative medicine and a branch of traditional Chinese medicine where fine needles are inserted into the patient’s body. The objective of this study was to identify in the literature, scientific evidence about the effectiveness of acupuncture in the relief of temporomandibular pain. To carry out this research, an integrative review of the literature was carried out, of a descriptive and exploratory nature, based on electronic research in the Virtual Health Library (VHL), in the scientific databases: LILACS, SCIELO, MEDLINE and BRISA. From the analysis of the literature, it was evidenced that acupuncture is effective because it acts directly on the hypothalamic-pituitary-adrenal axis, it is a therapy without contraindications, painless and low cost. In addition, the positive effects of acupuncture, helping in the therapy of chronic pain, from the release of opioids that act directly at the pain site, generally replacing the ingestion of drugs.